1981
DOI: 10.1159/000123141
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Age and Thyroid Hormone Status on Beta-Endorphin Content in Rat Corpus Striatum and Hypothalamus

Abstract: These studies investigated the effect of aging on thyroid hormone regulation of β-endorphin in rat corpus striatum and hypothalamus. In both brain areas, basal levels of β-endorphin declined with age. In addition, age modified the response of β-endorphin to thyroid hormone status. Hypothyroid rats aged 6 months (mature) exhibited a 67% mean decline in the level of β-endorphin in the corpus striatum. Hypothyroid rats aged 20–24 months (senescent) exhibited no change in the level of β-endorphin in the corpus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Mu-opioid receptor binding in the striatum, anterior cortex, and amygdala declines with aging (Messing et al, 1980), and ligands such as β-endorphin and enkephalin are sparser (Dupont et al, 1980; Gambert, 1981; Girardot and Holloway, 1985b). Age-related changes in opioid control of food intake have also been reported (Gambert, 1981; Girardot and Holloway, 1985a; Kavaliers et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mu-opioid receptor binding in the striatum, anterior cortex, and amygdala declines with aging (Messing et al, 1980), and ligands such as β-endorphin and enkephalin are sparser (Dupont et al, 1980; Gambert, 1981; Girardot and Holloway, 1985b). Age-related changes in opioid control of food intake have also been reported (Gambert, 1981; Girardot and Holloway, 1985a; Kavaliers et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Mu-opioid receptor binding in the striatum, anterior cortex, and amygdala declines with aging (Messing et al, 1980), and ligands such as β-endorphin and enkephalin are sparser (Dupont et al, 1980; Gambert, 1981; Girardot and Holloway, 1985b). Age-related changes in opioid control of food intake have also been reported (Gambert, 1981; Girardot and Holloway, 1985a; Kavaliers et al, 1985). However, more specific examinations of hedonic functions suggest that the ability of endogenous opioids to mediate the pleasure of eating sweets does not appear to decline in aging humans (Whichelow and Prevost, 1996) or rats (Islam et al, 1993), consistent with our finding that the hedonic impact of sucrose and corn oil was not altered in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…13, 18, 24], During maturation the hypo thalamic opioid peptide content increases dramatically [21], and the increase may progress between 3 and 6 months of age (table II). Furthermore, the content may depend on behavior [7], the health of the animal, or the hormonal sta tus of the animal [12]. These factors account for variability and the need for large numbers of animals, particularly in older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The proenkephalin A precursor codes for the enkephalin series of opioid peptides; the prodynorphin (proenkephalin B) precursor contains sequences for the dynorphins (DYN) 1-32, 1-29, 1-17, and 1-8 and also the neoendorphins and leucine enkephalin. These precursor molecules are widely distributed, including in the component tissues of the hypo thalamo-pituitary axis; their posttranslational processing differs between regions and is independently regulated between systems [22].The distribution (in terms of content/brain area) of the opioid peptides has been shown to change with age [2,10,12,13,15,18,19]. In C57BL/6J mice the content ofimmunoreactive (3-EP (ir-fiEP) and immunoreactive enkephalin…”
mentioning
confidence: 99%
“…Several reports have suggested that the endogenous opioid systems are modified in older animals. Methionine‐ and leucine‐enkephalin, as well as β‐endorphin and arg 6 phe 7 met‐enkephalin, have been reported to be present in lower concentrations in the hypothalamus of old than young rats 9–13 . β‐endorphin levels also have been reported to be decreased in a number of other areas within the CNS 14 .…”
Section: Opioids and Analgesiamentioning
confidence: 99%